PENGARUHPEMBERIAN PAKAN DENGAN LEVEL PROTEIN YANG BERBEDA TERHADAP ENERGI METABOLISME AYAM KAMPUNG - Erik Priyo Santoso; Eka Fitasari (BUANA SAINS, 2016)
The purpose of this research is to determine the level of protein stage that gives the best results against the metabolizable energy of Local Chickens. The results of this research are expected can be a consideration and information about the differences effect of the dietary protein provision to the digestibility of metabolizable energy in Local Chicken, especially in the "New" strain of Local Chickens.This research was conducted at the Field Laboratory of Animal Husbandry, University of Tribhuwana Tunggadewi, Malang and at the Laboratory of Animal Nutrition and Feed, Faculty of Animal Husbandry, the University of Brawijaya in January 2014 until February 2014. The method that used in this research was the biological experimental method and the materials that used are the local chicken which the result of cross-breeding between Kedu's chicken and Male Bangkok's chicken, with a number of materials are 20 materials and the each weight are 800 grams.The conclusion of this research shows that the value of Crude Protein (PK) is proportional to the metabolic energy's value, which is in this research shows that the lower Crude Protein value gives impact on the degradation of metabolizable energy. The metabolizable energy in the P2 treatment provides the best metabolizable energy in the Local Chicken. So it may be advisable to conduct the further research using the same objects and the studies are more diverse, given the object of the research is the "New" strain of Local Chicken.